Athelia Biodeiversity Fund Brazil (ABF-Brazil) - CGIAR Research Program on Climate Change, Agriculture and Food Security (2019)
Leveraging on our strategic partnership with Mirova Natural Capital investment advisor of the ABF Brazil (Brazilian Equity Fund) and USAID a US$100 million impact investment fund was designed to invest in innovative projects/companies to protect biodiversity/forest conservation, promote CSA and enhance livelihoods. It was launched on November 2019 in Belém.